Treatment satisfaction in multiple sclerosis - Glanz, Bonnie I; Musallam, Alexander; Rintell, David J; Chitnis, Tanuja; Weiner, Howard L; Healy, Brian C (International journal of MS care, 2014)
Disease-modifying therapies (DMTs) for the treatment of multiple sclerosis (MS) are associated with inconvenient methods of administration, significant side effects, and low adherence rates. This study was undertaken to compare treatment satisfaction in MS patients treated with interferon beta-1a intramuscular (IFNβ-1a IM), interferon beta-1a subcutaneous (IFNβ-1a SC), glatiramer acetate (GA), and natalizumab (NTZ), and to examine the associations between treatment satisfaction ratings and adherence to therapy. Two hundred twenty-six treated MS patients completed the Treatment Satisfaction Questionnaire for Medicine. Multivariable models were used to compare treatment satisfaction across groups. There were no statistically significant differences in overall treatment satisfaction. The NTZ group reported greater satisfaction with the ability of the medication to treat or prevent MS than the IFNβ-1a IM group. The NTZ group also reported higher overall convenience scores than the IFNβ-1a IM group and greater satisfaction with ease of use of the medication than the interferon and GA groups. Patients in the IFNβ-1a IM group reported less satisfaction with ease of planning when to use the medication than those in the other groups. Convenience was associated with adherence in IFNβ-1a SC- and GA-treated patients, with lower convenience scores associated with lower adherence. These results may be useful to MS patients and health-care providers facing decisions about DMT use.